2011
DOI: 10.1007/s12011-011-9275-7
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cell Cycle Arrest and Apoptosis by Ruthenium Complex cis-(Dichloro)tetramineruthenium(III) Chloride in Human Lung Carcinoma Cells A549

Abstract: Lung cancer is one of the leading causes of death in the world, and non-small cell lung carcinoma (NSCLC) accounts for approximately 75-85% of all lung cancers. In the present work, we studied the cytotoxic activity, cell cycle arrest and induction apoptosis of the compound cis-(dichloro)tetramineruthenium(III) chloride {cis-[RuCl(2)(NH(3))(4)]Cl} in human lung carcinoma tumor cell line A549. The results of MTT and trypan blue assays showed that cis-[RuCl(2)(NH(3))(4)]Cl causes reduction in the viability of A5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Therefore, the overall morphological analysis outcomes provided strong evidence of an apoptosis-inducing activity, in line with several in vitro studies supporting apoptotic events to explain the anticancer properties of different ruthenium derivatives, both in their +2 and +3 oxidation states [47,78,112,140,141,153,[155][156][157][158][159][160][161]. However, also other different molecular pathways can be involved in the cell death process [153].…”
Section: Cell Morphological Changes Induced By In Vitro Treatment Witsupporting
confidence: 73%
See 1 more Smart Citation
“…Therefore, the overall morphological analysis outcomes provided strong evidence of an apoptosis-inducing activity, in line with several in vitro studies supporting apoptotic events to explain the anticancer properties of different ruthenium derivatives, both in their +2 and +3 oxidation states [47,78,112,140,141,153,[155][156][157][158][159][160][161]. However, also other different molecular pathways can be involved in the cell death process [153].…”
Section: Cell Morphological Changes Induced By In Vitro Treatment Witsupporting
confidence: 73%
“…Therefore, the overall morphological analysis outcomes provided strong evidence of an apoptosis-inducing activity, in line with several in vitro studies supporting apoptotic events to explain the anticancer properties of different ruthenium derivatives, both in their +2 and +3 oxidation states. [47,78,112,140,141,153,[155][156][157][158][159][160][161] However, also other different molecular pathways can be involved in the cell death process. [153] In fact, in the case of MCF-7 cells treated with the DoHuRu/DOTAP liposomes at IC50 conc., in addition to apoptotic hallmarks, also autophagic vacuoles were clearly detectable, suggesting morphological changes associated with autophagy activation (Figure 9c, inset).…”
Section: Cell Morphological Changes Induced By In Vitro Treatment Witmentioning
confidence: 99%
“…10 They show less toxicity, they are selective of tumor cells, and present a novel mechanism of action, the prospect of non-cross-resistance and a different spectrum of activity. [11][12][13][14][15][16][17][18][19] In a previous study, we recently reported that complexes with the general formula [Ru(AA-H)(dppb)(bipy)] PF 6 (AA-H = amino acid anion) inhibited the growth of Ehrlich carcinoma cells in vitro. 20 Among the Ru(II)/ amino acid/diphosphine complexes evaluated, those with l-methionine and l-tryptophan present the best activity against Ehrlich carcinoma cells, with IC 50 values (concentration that results in a 50% reduction in cellular viability) of 10.2 ± 2.3 µM and 8.7 ± 3.1 µM, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…10 They show less toxicity, they are selective of tumor cells, and present a novel mechanism of action, the prospect of non-cross-resistance and a different spectrum of activity. 1119…”
Section: Introductionmentioning
confidence: 99%
“…The samples were incubated at 4°C in the dark and analyzed by flow cytometry (FACSCalibur, BD Biosciences, San José, CA, . The percentage of cells in phases sub-G1, G0/G1, S, and G2/M was analyzed using the ModFitLT software (Verity Software House, Topsham, ME, USA)[30].…”
mentioning
confidence: 99%